Students’ reflections on the effectiveness of their ESAP courses: A multidisciplinary evaluation at tertiary level - Hadjiconstantinou, Stavroulla; Papadima-Sophocleous, Salomi (My University, 2013)
This paper reports on the evaluation of English for Specific Academic Purposes (ESAP) programmes at a language centre of a newly established government university in the Republic of Cyprus. In particular, it describes the student evaluation of ten ESAP courses offered to first year students of all 10 departments of the University. This evaluation was carried out after 2 years of full implementation of all the programmes. Using quantitative methods, the investigation explored students’ opinion of different aspects of their ESAP course: skills development, course content, materials and tools, as well as pedagogical approaches. The purpose of the project was firstly to determine whether the courses, which were designed and implemented based on a combination of theoretical considerations, methods and approaches (constructivist approach, communicative method, task-based, ESP, CEFR, ICT integration, etc) are indeed relevant to the needs and interests of the students. Secondly the evaluation process was carried out to diagnose possible weaknesses of the courses so that the courses could be further developed and improved.
Keywords: ESP; ESAP; Tertiary education; Course evaluation: student expectations; Skills development; Course content; Materials and tools; Pedagogical approaches